Writing Strategies of Freshmen and Sophomore Students in a Tertiary Institution: Implications to English Teacher - Asio, John Mark; Mobo, Catherine; Anico, Mark Jaebel; Calderon, Arwill Antoine; Capistrano, Mika (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research aims to determine students' writing strategies in a tertiary institution in Olongapo City, Philippines. Seventy-two (72) college freshmen and sophomore students participated in the study. The researchers used a standardized survey questionnaire to gather pertinent data. Also, the researchers calculated the descriptive and inferential statistics using SPSS 20. The study results revealed that the student respondents have a